Molecular determinants of binding of non-oxime bispyridinium nerve agent antidote compounds to the adult muscle nAChR. (1st April 2021) - Epstein, Max; Bali, Karan; Piggot, Thomas J.; Green, A. Christopher; Timperley, Christopher M.; Bird, Mike; Tattersall, John E.H.; Bermudez, Isabel; Biggin, Philip C.
Highlights: Simulation of bispyridinium compounds at human nAChRs reveals interaction sites. Longer bispyridiniums can also interact at an allosteric site. Two-electrode voltage clamp recordings confirm the simulations. Abstract: Organophosphorus nerve agents (NAs) are the most lethal chemical warfare agents and have been used by state and non-state actors since their discovery in the 1930s. They covalently modify acetylcholinesterase, preventing the breakdown of acetylcholine (ACh) with subsequent loss of synaptic transmission, which can result in death. Despite the availability of several antidotes for OPNA exposure, none directly targets the nicotinic acetylcholine receptor (nAChR) mediated component of toxicity. Non-oxime bispyridinium compounds (BPDs) have been shown previously to partially counteract the effects of NAs at skeletal muscle tissue, and this has been attributed to inhibition of the muscle nAChR. Functional data indicate that, by increasing the length of the alkyl linker between the pyridinium moieties of BPDs, the antagonistic activity at nAChRs can be improved. Molecular dynamics simulations of the adult muscle nAChR in the presence of BPDs identified key residues likely to be involved in binding. Subsequent two-electrode voltage clamp recordings showed that one of the residues, εY131, acts as an allosteric determinant of BPD binding, and that longer BPDs have a greater stabilizing effect on the orthosteric loop C than shorter ones. The work reported will inform future design work on novel antidotes for treating NA exposure.